PENGARUH SEGREGASI KELAS TERHADAP MOTIVASI BELAJAR FIQIH KELAS VIII DI MTs NW TEKO TAHUN PELAJARAN 2024/2025 - Marliyani, Novia; Supriyanto, Supriyanto; Suhamdi, Suhamdi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
In the learning process, the interaction between male and female students in the classroom becomes a competitive force for learning, and even tends to compare each other's abilities and intelligence in learning. However, it is still often found that students' motivation to learn in fiqh lessons is disturbed. Class segregation is or classifies based on gender is an effort that aims to further maximize students' motivation to learn and concentration in fiqh subjects. The objective of this research is to determine the effect of class segregation on the motivation in fiqh among grade VIII at MTs NW Teko. This research is a type of quantitative research with an ex-post facto design. The data analysis technique applied is simple linear regression, processed using the SPSS for windows version 30.0 program. The results of this study show that there is an effect of class segregation on the motivation to learn fiqh in grade VIII at MTs NW Teko with the value obtained t calculated is greater than that of the t table (2.088 > 2.037) with a significance level value of less than 0.05 (0.045 < 0.05) and that H0 is rejected and Ha is accepted. Therefore, it can be interpreted that the class segregation(X) affects the motivation to learn fiqh(Y).